Defect processes in F and Cl doped anatase TiO(2) - Filippatos, Petros-Panagis (Sci Rep, 2019)
Titanium dioxide represents one of the most widely studied transition metal oxides due to its high chemical stability, non-toxicity, abundance, electron transport capability in many classes of optoelectronic devices and excellent photocatalytic properties. Nevertheless, the wide bang gap of pristine oxide reduces its electron transport ability and photocatalytic activity. Doping with halides and other elements has been proven an efficient defect engineering strategy in order to reduce the band gap and maximize the photocatalytic activity. In the present study, we apply Density Functional Theory to investigate the influence of fluorine and chlorine doping on the electronic properties of TiO(2). Furthermore, we present a complete investigation of spin polarized density functional theory of the (001) surface doped with F and Cl in order to elaborate changes in the electronic structure and compare them with the bulk TiO(2).